An investigation on the dynamic characteristics of a two-dimensional piston flowmeter. (April 2022) - Ding, Chuan; Chen, Hao-qi; Zhang, Li-chao; Xia, Ning; Ruan, Jian
The immediate measurement of dynamic flow rate is of importance in the modern hydraulic system. Following a brief review and analysis on measuring methods of dynamic flow rate, authors introduced the structure and working principle of a two-dimensional piston dynamic flowmeter. Consequently, a mathematical model was carefully established based on its unique mechanical properties due to the two degrees of working freedom. Meanwhile, the transform function is obtained to describe the dynamic characteristics and used to discuss influences from various design parameters. Finally, a 3D printed prototype was designed and fabricated to measure the sinusoidal flow rate with the frequency range of 1–7 Hz on a calibration test rig. The discrepancy between the experimental and the simulated date is quite foreseeable considering the major influence of low oil bulk modulus due to air bubbles. Although the magnitude reaches −3 dB at 4 Hz, the dynamic characteristics are acceptable and can verify the feasibility of applying the two-dimensional piston flowmeter on the dynamic measurement field. The shortcomings of this prototype are well discussed in the conclusion part to provide guidance to enhance the design ability of next-generation prototypes.